Dysregulation of Mesenchymal Cell Survival Pathways in Severe Fibrotic Lung Disease: The Effect of Nintedanib Therapy - Kasam, Rajesh K.; Reddy, Geereddy B.; Jegga, Anil G.; Madala, Satish K. (Frontiers in Pharmacology, 2019)
Impaired apoptotic clearance of myofibroblasts can result in the continuous expansion of scar tissue during the persistent injury in the lung. However, the molecular and cellular mechanisms underlying the apoptotic clearance of multiple mesenchymal cells including fibrocytes, fibroblasts and myofibroblasts in severe fibrotic lung diseases such as idiopathic pulmonary fibrosis (IPF) remain largely unknown. We analyzed the apoptotic pathways activated in mesenchymal cells of IPF and in a mouse model of TGFα-induced pulmonary fibrosis. We found that fibrocytes and myofibroblasts in fibrotic lung lesions have acquired resistance to Fas-induced apoptosis, and an FDA-approved anti-fibrotic agent, nintedanib, effectively induced apoptotic cell death in both. In support, comparative gene expression analyses suggest that apoptosis-linked gene networks similarly dysregulated in both IPF and a mouse model of TGFα-induced pulmonary fibrosis. TGFα mice treated with nintedanib show increased active caspase 3-positive cells in fibrotic lesions and reduced fibroproliferation and collagen production. Further, the long-term nintedanib therapy attenuated fibrocyte accumulation, collagen deposition, and lung function decline during TGFα-induced pulmonary fibrosis. These results highlight the importance of inhibiting survival pathways and other pro-fibrotic processes in the various types of mesenchymal cells and suggest that the TGFα mouse model is relevant for testing of anti-fibrotic drugs either alone or in combination with nintedanib.